DEVELOPMENT OF PERFORMANCE ASSESSMENT INSTRUMENTS FOR PERIODIC MAINTENANCE OF ROAD SWEEPERS (ATIKANOTO: Journal of Automotive Engineering Education, 2024)
The purpose of this research is to make performance assessments on the competence of periodic maintenance of heavy equipment road sweepers. The performance assessment material created has been validated by experts. This research uses the 4-D development model, namely define, design, develop, disseminate. The research subjects consisted of subject teachers and mechanics from industry. The data collection technique in this thesis used a performance assessment instrument which was analyzed by CVR (content validity ratio) and CVI (content validity index) methods. The results showed that the performance assessment product for road sweeper periodic maintenance competency obtained a CVR value of 15.33 and a CVI value of 0.958. These values are declared valid and suitable for use in learning activities at school. Tujuan penelitian ini yaitu pembuatan asesmen kinerja pada kompetensi perawatan berkala road sweeper alat berat. Materi asesmen kinerja yang dibuat telah divalidasi oleh para ahli. Penelitian ini menggunakan model pengembangan 4-D, yaitu define, design, develop, disseminate. Subjek penelitian terdiri dari guru mata pelajaran dan mekanik dari industri. Teknik pengumpulan data dalam skripsi ini menggunakan instrumen asesmen kinerja yang dianalisis dengan metode CVR (content validity ratio) dan CVI (content validity index). Hasil penelitian menunjukkan bahwa produk asesmen kinerja untuk kompetensi perawatan berkala road sweeper memperoleh nilai CVR sebesar 15,33 dan nilai CVI sebesar 0,958. Nilai-nilai ini dinyatakan valid dan layak untuk digunakan dalam kegiatan belajar di sekolah.